Speech of Justice McKinnon: Induction Into the Common Law Honour Society - McKinnon, Colin (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
The Remarks of the Honourable Colin McKinnon, K.C., former Justice of the Ontario Superior Court of Justice, at his induction into the Common Law Honour Society in Ottawa on September 13, 2023.